Synthesis, Molecular Docking and Biological Evaluation of Novel Chlorobenzenesulfonamide Analogues of Ibuprofen as Anti-Bacterial, Anti-Diabetic and Anti-Alzheimer Agents - Adina Tatheer; Shahzad Murtaza; Naghmana Kausar; Hammad Ismail; Safeer Ahmed (International Journal of Cheminformatics, 2025)
In this work, we have synthesized novel chlorobenzensulfonamide tertiary amide based analogues of Ibuprofen (Ibu) and investigated them for their anti-bacterial, anti-diabetic and anti-Alzheimer activities. In the first step, Ibu was converted to amide derivatives by incorporating different aromatic amines. These were further converted into sulfonamide analogues (Sul-Ibu, 1-9) by treating it with p-chlorobenzensulfonyl chloride. Sul-Ibu (1-9) were screened against S. aureus, B. subtilis, S. mutans, E. coli, P. aeruginosa, S. epidermidis, A. odontolyticus, B. halodurans, and M. luteus. The analogues 4, 7-9 showed significant results as compared to Ibu due to the presence of sulfonamide moiety. The anti-diabetic efficacy was also determined by testing the inhibitory potency against diabetes causing enzymes (α-amylase and α-glucosidase) and found 4 (IC50 61.80±0.85 µg/mL) and 5(IC50 53.75±0.79 µg/mL) as most promising agents. Sul-Ibu analogues also exhibited impressive inhibition profiles as Anti-Alzheimer agents. Compound 7 appeared to be the most potent one providing the percentage inhibition 95.8±0.31 against AChE and 96.7±0.16 against BChE. Additionally, this analogue also provided Ki value 27 µmol. Molecular docking study with α-amylase, α-glucosidase, AChE and BChE were also in good accordance to that of experimental results. These results clearly indicate that Sul-Ibu analogues appeared promising antibacterial, antidiabetic and anti-Alzheimer agents and should be considered for clinical studies.
Keywords: Synthesis; anti-bacterial; anti-cholinesterase; anti-diabetic; α-amylase; α-glucosidase